Placebo Responses and Placebo Effects in Functional Gastrointestinal Disorders - Enck, Paul; Klosterhalfen, Sibylle (Frontiers in Psychiatry, 2020)
Much has been written about the placebo effects in functional gastrointestinal disorders (FGD), especially in irritable bowel syndrome (IBS), driven by the early hypothesis that in randomized controlled trials (RCTs) of IBS, the placebo effect might be specifically high and thus, corrupts the efficacy of novel drugs developed for this condition. This narrative review is based on a specific search method, a database (www.jips.online) developed since 2004 containing more than 4,500 papers (data papers, meta-analyses, systematic reviews, reviews) pertinent to the topic placebo effects/placebo response. Three central questions—deducted from the body of current literature—are addressed to explore the evidence behind this hypothesis: What is the size placebo effect in FGD, especially in IBS, and is it different from the placebo effect seen in other gastrointestinal disorders? Is the placebo effect in FGD different from other functional, non-intestinal disorders, e.g. in other pain syndromes? Is the placebo effect in FGD related to placebo effects seen in psychiatry, e.g. in depression, anxiety disorders, and alike? Following this discussion, a fourth question is raised as the result of the three: What are the consequences of this for future drug trials in FGD? In summary it is concluded that, contrary to common belief and discussion, the placebo effect seen in RCT in FGD is not specifically high and extraordinary as compared to other comparable (i.e. functional) disorders. It shares less than expected commonalities with the placebo effect in psychiatry, and very few predictors have yet been identified that determine its effect size, especially some that are driven by design features of the studies. Current practice of RCT in IBS seems to limit and control the placebo effect quite well, and future trial practice, e.g. head-to-head trial, still offers options to maintain this control, even in the absence of placebos used.